PERANCANGAN APLIKASI DESTINASI WISATA GLODOK PANCORAN BERBASIS WEB - Angelica Christina; Tony; Teny Handhayani (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
The study focuses on the development of a web-based application designed to promote the Glodok Pancoran tourist destination in Jakarta, Indonesia. The primary aim is to enhance visitor experiences by providing comprehensive information on local culture, cuisine, and transportation options. The research employs a systematic design process involving use case, activity, sequence, and class diagrams for process planning, alongside conceptual and logical database design. The application highlights a user-friendly interface with sections dedicated to heritage destinations, culinary experiences, religious sites, virtual tours, transportation, news, and reviews. The application utilizes Next.js for the front end and Golang with MySQL for the back end, adhering to the Agile methodology. Research methods included surveys and interviews with village representatives, which highlighted a significant interest in Chinese culture and cuisine and identified a need for improved information on transportation and local attractions. The project successfully increases awareness and accessibility of Glodok Pancoran, positioning it as a prominent tourist destination.